Performance of UAV Image for Flood Mapping with 2 Dimensional Model in Kaliputih River, Panti District - Icha Derka; Entin Hidayah; Gusfan Halik (Department of Geography Education, University of Jember, 2022)
In January 2006, the flash flood in Panti Sub-district was a national disaster, causing damage to building infrastructure and fatalities. From this incident, it is necessary to have flood mitigation by providing a map of the distribution of flood inundation using a 2D hydraulic model to provide information regarding the extent of flood inundation in the study area. Due to the limited DEM data for 2D modeling, it is necessary to use UAV images to provide a DSM with good and higher resolution. This study aims to assess the performance of 2D flood modeling results using HEC-RAS equipped with RAS Mapper through UAV processing as input. There are 21 GCP in the study area as an increase in accuracy, the RMSE value in the horizontal direction is 0.3853m, and the vertical direction is 0.1836m. From the CE90 accuracy test results for a horizontal accuracy of 0.58m and LE90 for a vertical accuracy of 0.30m, it can be concluded that the map accuracy test meets the 1:2500 scale. Terrain maps are input to HEC-RAS; selected meshes are 5x5m and 2x2m. The modeling results can show the inundation depth in each GCP from the min-max depth. The model calibration shows an RMSE value of 0.183, while the flood depth validation shows an RMSE value of 0.13. In other words, modeling can represent the distribution of flood inundation in the study area and provide benefits for the community to be more alert in the event of a flood in the coming year. Keywords : UAV; GCP; DSM; HEC-RA; Flood mapping Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License